2002
DOI: 10.1021/ja020984n
|View full text |Cite
|
Sign up to set email alerts
|

C3-Symmetrical Supramolecular Architectures:  Fibers and Organic Gels from Discotic Trisamides and Trisureas

Abstract: Hydrogen bonded C(3)-symmetrical molecules that associate into supramolecular stacks are described. Structural mutation on these molecules has been performed to elucidate the contribution of the different secondary interactions (hydrogen bonding, pi-pi stacking) to the self-assembly of the disks into chiral stacks. Twelve C(3)-symmetrical molecules have been investigated, six of which contain three central amide functionalities (1a-f) and six of which contain three central urea groups (2a-f). Peripheral groups… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
281
0
10

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 449 publications
(298 citation statements)
references
References 19 publications
7
281
0
10
Order By: Relevance
“…5 for calculation details). The structure resembles the C3 symmetric helical supramolecular structures based on 1,3,5-benzenetricarboxylic acid and others thoroughly studied by Meijer and colleagues [33][34][35] .…”
Section: Resultsmentioning
confidence: 58%
“…5 for calculation details). The structure resembles the C3 symmetric helical supramolecular structures based on 1,3,5-benzenetricarboxylic acid and others thoroughly studied by Meijer and colleagues [33][34][35] .…”
Section: Resultsmentioning
confidence: 58%
“…4). 58 Molecuar modeling studies and an X-ray structural analysis strongly supported the curved and coplanar conformation of the helical backbone. This curvature lead to a helical arrangement for longer oligomers with lengths exceeding 7-9 units, where it is proposed that p-p interactions further stabilize the helical architecture once a turn is completed.…”
Section: Foldamers From Oligomers and Polymersmentioning
confidence: 79%
“…[53][54][55][56] and Meijer and coworkers, [57][58][59] where p-p stacking interactions combined with hydrogen-bonding interactions direct folding. Huc and coworkers reported that oligoamide strands composed of alternating 2,6-bis(carbonylamino) pyridine units and 2,6-pyridinedicarboxamide units selforganized into single stranded helical structures upon forming intramolecular hydrogen bonds (Fig.…”
Section: Foldamers From Oligomers and Polymersmentioning
confidence: 99%
“…Examples are binding of mercury ions to helical oligomeric cholates 23 and the induction of helicity in oligo-(meta-ethynylpyridine)s upon binding of saccharides. 24 From a fundamental point of view, the intrinsic folding dynamics 25 of these molecules can provide insight into the more complex folding behavior of proteins as foldamers are composed of a single monomer.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, we reported a new class of poly(ureidophthalimides) (PUP, 1) illustrated in Figure 1, which was shown to fold in apolar and polar media [25][26][27] depending on the nature of the R* group. The NH-groups of the ureas, which are positioned at the 3,6-positions of phthalimide ring, preferentially adopt a conformation in which intramolecular hydrogen bonding of the NH protons with the adjacent imide oxygens is operational.…”
Section: Introductionmentioning
confidence: 99%